2008
DOI: 10.1186/ar2375
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker profiles in serum and saliva of experimental Sjögren's syndrome: associations with specific autoimmune manifestations

Abstract: Introduction Sjögren's syndrome (SS) is a systemic autoimmune disease that mainly targets the exocrine glands. The aim of this study was to investigate the involvement of 87 proteins measured in serum and 75 proteins analyzed in saliva in spontaneous experimental SS. In addition, we intended to compute a model of the immunological situation representing the overt disease stage of SS. Methods Nondiabetic, nonobese diabetic (NOD) mice aged 21 weeks were evaluated for sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 50 publications
1
57
1
1
Order By: Relevance
“…This observation supports the hypothesis that acinar cells are involved actively in the pathogenesis of SS and provides new evidence to the search of early biomarkers for diagnosis and/or disease activity. At the prediabetic stage, the non-obese diabetic (NOD) mouse model of Sjögren's syndrome has the unique characteristic of developing a deep secretory dysfunction with mild infiltration of the glands [9][10][11] consistent with a structural-dysfunctional aetiology. In keeping with this, early neurotransmitter receptor-signalling alterations have been reported in NOD females' submandibular glands unrelated to the onset of the autoimmune response [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This observation supports the hypothesis that acinar cells are involved actively in the pathogenesis of SS and provides new evidence to the search of early biomarkers for diagnosis and/or disease activity. At the prediabetic stage, the non-obese diabetic (NOD) mouse model of Sjögren's syndrome has the unique characteristic of developing a deep secretory dysfunction with mild infiltration of the glands [9][10][11] consistent with a structural-dysfunctional aetiology. In keeping with this, early neurotransmitter receptor-signalling alterations have been reported in NOD females' submandibular glands unrelated to the onset of the autoimmune response [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests that a remodeling of the vasculature in the salivary glands may not be necessary to facilitate chronic hyperemia. Additionally, reported findings on protein expression levels of vascular endothelial growth factor (VEGF, an initiator of angiogenesis) have been contradictory, with some studies displaying an increase (Ohno et al 2004;Sisto et al 2012) and others no change or a decrease in expression (Delaleu et al 2008;Szodoray et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been shown that some patients with SS have increased blood flow (hyperemia) through their major salivary glands, as compared with that of healthy 573323J HCXXX10.1369/0022155415573323McCall and BakerAngiogenesis in Sjögren's Syndrome research-article2015 individuals (Chikui et al 2000;Steiner et al 1994). This finding is suggestive of blood vessel growth and remodeling (angiogenesis), and has led to numerous studies investigating pro-angiogenic factors in patients with SS (Delaleu et al 2008;Ohno et al 2004;Sisto et al 2012;Szodoray et al 2004). However, no previous studies have directly analyzed the vascular organization of salivary glands with SS for signs of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…PATHOGENESIS SS is characterized by epithelial cell destruction and peri-epithelial infiltration by T CD4 lymphocytes and a lower number of B lymphocytes 14 with multiple target organs, particularly exocrine glands. Th2 cytokines have been found to be involved in an early stage of the disease, while Th1 cytokines appear at an advanced stage 15 .…”
Section: Introductionmentioning
confidence: 99%